Land-Locked:: A Critique of Kevin Carson on Property Rights - Long, Roderick T. (2015)
Long examines the nature of property rights from the perspective of the requirements imposed by the residual rights of the community at large; for Georgians, the community itself plays an active role, for example, the famous Henry George’s “Single Tax” on land values, while mutualism, in the tradition of Benjamin Tucker, tend to view the free land as only those communal land without owner, over which the latter property rights of mankind are dormant. Long criticizes the view of Kevin Carson – on the pragmatic benefits of mutualism on the Georgians and Lockean rivals – as a philosopher, restricting his attention to a philosophical problem concerning property rights he identifies in that author. The central point of contention is that, in the view of Long, the Lockean approach is the only defensible under the libertarian point of view.